Analisis Produktivitas Alat Berat Untuk Pekerjaan Galian Pada Proyek Pembangunan Jalan Tepus-Jerukwudel II (STA 25+100-25+225) - Rizky Nugrahing Nur Assyifa; Budi Priyanto (Politeknik Negeri FakFak, 2022)
Technically, heavy equipment resources are the main factor in implementing a road project. The use of heavy equipment is urgently needed in the process of accelerating the implementation of road works in accordance with predetermined targets. In this project there are several stages of work planned and implemented, one of which is earthworks. Earthworks include excavation work that requires Rock Drill Breaker heavy equipment to speed up work time. This research was conducted at the Tepus-Jerukwudel Road Development Project Phase II, Gunungkidul Regency, with the aim of knowing the work productivity of heavy equipment and knowing the time needed for heavy equipment to complete excavation work. The method used is the manual calculation method using the productivity formula, time calculation and soil excavation volume calculation to produce the effective time during the use of Rock Drill Breaker . Based on the results of productivity calculations on excavation work using a Rock Drill Breaker with an hourly production of 23.86 m3/hour, daily production of 166.9 m3/day with a time of 83 days. The results of this study indicate that good management and utilization of heavy equipment can accelerate the expected target time.